Characterizing postoperative physiologic swallow function following transoral robotic surgery for early stage tonsil, base of tongue, and unknown primary human papillomavirus‐associated squamous cell carcinoma. Issue 5 (5th February 2021) - Ottenstein, Lauren; Cornett, Hannah; Switchenko, Jeffrey M.; Nathan, Meghana; Thomas, Susan; Gillespie, Amanda I.; McColloch, Nancy; Barrett, Tiffany; Studer, Matthew B.; Brinkman, Meghan; Kaka, Azeem S.; Boyce, Brian J.; et al.
Abstract: Background: Data objectively evaluating acute post‐transoral robotic surgery (TORS) swallow function are limited. Our goal was to characterize and identify clinical variables that may impact swallow function components 3 weeks post‐TORS. Methods: Retrospective cohort study. Pre/postoperative use of the Modified Barium Swallow Impairment Profile (MBSImP) and Penetration‐Aspiration Scale (PAS) was completed on 125 of 139 TORS patients (2016–2019) with human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma. Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) scores were retrospectively calculated. Uni/multivariate analysis was performed. Results: Dysfunctional pre‐TORS DIGEST scores were predictive of post‐TORS dysphagia ( p = 0.015). Pre‐TORS MBSImP deficits in pharyngeal stripping wave, swallow initiation, and clearing pharyngeal residue correlated with airway invasion post‐TORS based on PAS scores ( p = 0.012, 0.027, 0.048, respectively). Multivariate analysis of DIGEST safety scores declined with older age ( p = 0.044). Odds ratios (ORs) for objective swallow function components after TORS were better for unknown primary and tonsil primaries compared to base of tongue (BOT) (OR 0.35–0.91). Conclusions: Preoperative impairments in specific MBSImP components, older patients, and BOT primaries may predict more extensive recovery in swallow function after TORS.